Cumulative Versus Alternative Conditions: A Study of Polygyny Permits in Indonesia From the Perspective of the Legal Certainty Principle - Abdul Helim; Aris Sunandar Suradilaga; Wafit Syuja' Vennovary Benevolent; Rabiatul Adawiyah (De Jure: Jurnal Hukum dan Syari'ah, 2023)
This paper aims to examine the conflict of authority between the alternative and the cumulative conditions stipulated in Law Number 1 of 1974 concerning Marriage, especially under the polygyny permit section. In this normative study, the problem is focused on the alternative conditions that determine the cumulative conditions and the analysis took into account the critical legal studies and adz-Dzari’ah theories, revealing that the alternative conditions are not appropriate to be determinant that allows polygyny to take place. Instead, these conditions are supposed to be additional or optional. Conversely, the more appropriate condition as the polygyny permit determinant is cumulative. Similarly, in the analysis of the adz-Dzari’ah theory, when the alternative condition is the determinant, it will bring harm instead, meaning that it is included in the category sadd adz-Dzari’ah (prohibited or even forbidden). It is advisable to make the cumulative conditions the determinant of polygyny permits because it carries more benefits that allow for easier polygyny as it is included in the category fath adz-Dzari'ah. If there are requirements, they are still within reasonable limits that can be pursued. In addition, polygynous marriage can be performed before the Marriage Registrar witnessed by the first wife.